The Distributional Effects of Peer and Aspirational Pressure - Konstantinos Angelopoulos; Spyridon Lazarakis; Jim Malley (Center for Economic Studies and ifo Institute (CESifo), 2019)
We develop a theoretical framework where the cross-sectional distributions of hours, earnings, wealth and consumption are determined jointly with a set of expenditure targets defining peer and aspirational pressure for members of different social classes. We show existence of a stationary socio-economic equilibrium, under idiosyncratic stochastic productivity and socio-economic class participation. We calibrate a model belonging to this framework using British data and find that it captures the main patterns of inequality, between and within the social groupings. We find that the effects of peer pressure on within-group inequality differ between groups. We also find that wealth and consumption inequality increase within groups who aspire to match social targets from a higher class, despite a reduction in within-group inequality in hours and earnings.
Keywords: E21; E25; D01; D31; 330; inequality; incomplete markets; peer pressure; aspirations